Homocysteine enhances the excitability of cultured hippocampal neurons without altering the gene expression of voltage-gated ion channels - Alzbeta Filipova; Matus Tomko; Katarina Ondacova; Lucia Dubiel-Hoppanova; Nikola Chmúrčiaková; Leoš Cmarko; Robin N. Stringer; Norbert Weiss; Lubica Lacinova (Molecular Brain)
Abstract Elevated plasma homocysteine (Hcy) levels lead to hyperhomocysteinemia, a condition associated with various neurological disorders affecting multiple brain regions, including the hippocampus. In this study, we investigated the effects of exposing cultured rat hippocampal neurons to Hcy concentrations corresponding to mild, moderate, and severe hyperhomocysteinemia. A short 24-hour exposure had minimal effects, whereas prolonged exposure up to 14 days moderately enhanced hippocampal excitability without altering the gene expression of voltage-dependent calcium, sodium, or potassium channels or intracellular calcium levels. These findings suggest that Hcy-induced changes in neuronal excitability may contribute to neuropathologies associated with hyperhomocysteinemia.